ANALISIS PERAN PARTISIPASI PEREMPUAN SECARA EKONOMI DAN SOSIAL DI PESISIR PANTAI MUNCAR BANYUWANGI - Pahlevi, Riza; Jauhariyah, Nur Anim (Jurnal Ekonomi Syariah Darussalam, 2022)
The main problem that is often associated with resource management in coastal areas is the weak involvement of interested parties in the implementation of marine and coastal development. The purpose of this study was to analyze the role of women's participation economically and socially on the Muncar coast of Banyuwangi. The method used in this study uses a qualitative approach with research instruments of observation, interviews, and documentation. The results show that young coastal women have a strategic role in managing and planning for the sustainability of the family economy because they have a dual role as housewives and family "operators". However, the dual roles of these young coastal women are not equipped with advanced knowledge, mindset and behavior so that the level of economy and welfare of coastal communities is generally relatively low.